2020
DOI: 10.1080/23802359.2020.1811174
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA analysis of critically endangered Chinese Pangolins (Manis pentadactyla) from Nepal

Abstract: Chinese Pangolins (Manis pentadactyla) are Critically Endangered and one of the most illegally traded mammals globally. We generated first COI sequences from five individuals of this species from Nepal. BLASTn search of our 600 bp sequences at GenBank showed pair-wise identity between 99.17% and 100% to M. pentadactyla. There were three haplotypes and a total of five variable sites among five M. pentadactyla sequences. Neighbor-joining tree revealed that all M. pentadactyla from Nepal clustered into same group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Further analyses confirmed that pangolins from Nepal were also included in the MPB mt population (Shrestha et al. 2020).…”
Section: Conservation Geneticsmentioning
confidence: 73%
“…Further analyses confirmed that pangolins from Nepal were also included in the MPB mt population (Shrestha et al. 2020).…”
Section: Conservation Geneticsmentioning
confidence: 73%